Transfer Characteristic Analysis and Experimental Research of Asynchronous Axial Magnetic Coupler at High Speed - Li Wanjie; Zhang Guomin; Ai Liwang; Liu Guole; Gao Zhiyuan (Jixie chuandong)
The torque of magnetic couplers can be transferred by utilizing the magnetic field coupling,which changes the rigid connection into non-contact soft connection. It has the advantages of soft starting,vibration reduction,locked-rotor protection,high reliability,and is applied in industry. The magnetic couplers can also be used in specific conditions,such as superconducting flywheel energy storage system（ SFESS）,which can realize the motor placed out of vacuum chamber with no need for stator cooling system,the completely dynamic sealing of vacuum chamber,and long time energy storage. Due to rare application and research in the condition of high speed for magnetic couplers,the transfer characteristics at high speed of asynchronous axial magnetic coupler is studied based on the application of SFESS. The finite element model is built by using the general simulation method based on slip speed,the performance parameters of transferred torque,axial force,and magnetic flux density in the air-gap are calculated,and the temperature rise characteristic of critical components is analyzed. The prototype is manufactured,and the test platform of transfer characteristics at high speed is established. The experiments are conducted at the synchronous speed 9 500 r/min and the conventional modeling method is validated by comparing the experimental results with simulated results. Also the torque transfer characteristic at various speeds is compared. The feasibility of asynchronous axial magnetic coupler for high speed application is validated.